Literature Review: The Effect of Temperature on Hydrocracking of Pandanus Julianetti Oil Into Gasoline Fraction Using Ni/Modified Natural Zeolite Catalyst - Salim, Ilham; Supeno, Supeno (Journal of Health, Education, Economics, Science, and Technology (J-HEST), 2024)
This literature review investigates the effect of temperature on the hydrocracking of Pandanus Julianetti oil into gasoline fractions utilizing nickel (Ni) and modified natural zeolite catalysts. Hydrocracking is a vital process for converting biomass into valuable fuels, and temperature plays a crucial role in optimizing yield and efficiency. The review synthesizes findings from various studies, emphasizing advancements in catalyst development and the impact of operational conditions on product distribution. Results indicate that higher temperatures generally enhance conversion rates and gasoline yield, although optimal conditions vary based on catalyst composition and feedstock characteristics.